Growth, nodulation, yield, nitrogen uptake, and economics of lentil as influenced by sowing time, tillage, and management practices - Mukherjee, Bishal; Kumar Naskar, Manish; Nath, Rajib; Atta, Kousik; Visha Kumari, Venugopalan; Banerjee, Purabi; Alamri, Saud; Patra, Kiranmoy; Laing, Alison M.; Skalicky, Milan; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
Crop management practices and variety are two very important parameters that decides the crop performance. A field experiment was carried out during the two consecutive rabi seasons of 2018–19 and 2019–20 to determine the impact of sowing timing, tillage operation, and variety on the growth, development, yield characteristics, and nitrogen uptake in lentil crops. The experiment was conducted in a split-split plot design with 3 replications comprising two different sowing conditions (S1: early sowing after harvesting of short duration kharif rice, S2: delayed sowing after harvesting of long duration kharif rice) in main plots, three different tillage operations (T1: Relay cropping, T2: Zero tillage, T3: Conventional tillage) in subplots and two different varieties (V1: short duration: L4717, V2: long period: Moitri) in subplots. The findings demonstrated a substantial interaction between sowing time, tillage, and variety on various growth and yield parameters of lentil crops. The early sowing of lentil crops (early November) yielded 4.8% more (1,105 kg ha−1) than late November sowing and adapting to the short-duration variety L4717 over the long-duration cultivar Moitri resulted in a yield increase of 5.9% (1,086 kg ha−1). Apart from providing a higher yield, it also provided an opportunity to take another crop like leafy vegetables. Among the three tillage practices adopted, conventional tillage produced the lowest yield (1,017 kg ha−1) in both experimental years. In contrast, a yield increase of 6.9% and 26.9% in relay cropping and zero tillage systems was observed, respectively. Early-sown lentils with no-tillage and a short-duration variety reached a certain phenophase faster than other combinations (life cycle: 96.2 and 98.7 days for lentils in both years). For both the sowing times, the growth parameters and the number of nodules plant−1 were highly correlated with nitrogen uptake at different stages of the life cycle. High net returns (Rs. 51,220 and 59,257) leading to higher benefit-cost ratios were observed under the treatment combination of early sowing + zero tillage + short duration variety. Therefore, the study found that short-duration lentil cultivars in combination with early sowing in the zero-tillage system are the best agronomic approach for the sustainability of lentil production after the monsoon rice harvest.